Silent Branding and Consumer Perception: A Phenomenological Study of the Formation of Implicit Brand Recognition in Fashion Brands - Achmad Ridha; Hasnidar (Masterpiece, 2025)
This study investigates how silent branding shapes implicit brand recognition among fashion consumers in Makassar, focusing on minimalist brands such as Uniqlo, H&M, and Executive. Employing a transcendental phenomenology approach, the research explores consumers’ lived experiences in recognizing brands without relying on logos or explicit visual markers. Twelve purposively selected participants were interviewed in-depth, and data were analyzed through phenomenological reduction, including horizonalization, meaning-unit clustering, and textural–structural synthesis. Findings reveal that implicit brand recognition emerges through the interplay of four dimensions: (1) product design as an implicit identity, including cutting, silhouette, color palette, and material texture; (2) sensory familiarity developed through repeated physical interaction and use; (3) visual exposure across retail and social media environments that reinforces internalized aesthetic schemas; and (4) consistency in aesthetic and material quality across collections, which enhances perceived trust and brand credibility. The study demonstrates that minimalist brands can cultivate strong brand identity without logos when consistent design and sensory cues are reinforced by repeated exposure. This research extends the understanding of consumer perception by highlighting how memory, multisensory experience, and aesthetic consistency contribute to implicit recognition. Practically, the findings suggest that fashion brands adopting minimalist strategies can leverage silent branding to establish meaningful consumer connections, emphasizing experiential cues over overt visual symbols.